Engaging Nurses in the Design and Adoption of mHealth Tools for Care Coordination. - Murphy, Judy (Studies in Health Technology & Informatics, 2016)
This panel will share ideas for the Nursing Informatics Specialists in the audience on how mHealth tools are being designed and used for clinical practice, education and research. They will describe specific mHealth projects they are involved in, give practical examples, and provide tangible tactics for nurses to make a difference. They will provide insight into new technology and standards developments that make it easy to connect the mobile app ecosystem - from open application program interfaces (APIs), to traditional health information technology tools like Electronic Health Records (EHRs).